2006
DOI: 10.1159/000095290
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Soluble Human Leukocyte Antigen G Levels in Asthmatic Children

Abstract: Background: Human leukocyte antigen G (HLA-G) is a nonclassical major histocompatibility complex class I gene. HLA-G stimulates Th2 cytokine secretion by peripheral blood mononuclear cells. The role of soluble HLA-G (sHLA-G) in bronchial asthma is incompletely understood and the plasma level of sHLA-G in asthmatic children has not been investigated. Objective: It was the aim of this study to investigate the plasma level of sHLA-G in asthmatic children. Methods: Asthmatic (n = 53) and healthy children (n = 16) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 35 publications
5
46
0
2
Order By: Relevance
“…However, when the analysis was restricted to atopic asthmatics, sHLA-G levels were significantly higher in patients than in healthy controls (50).…”
Section: I) Immune-mediated Disordersmentioning
confidence: 87%
“…However, when the analysis was restricted to atopic asthmatics, sHLA-G levels were significantly higher in patients than in healthy controls (50).…”
Section: I) Immune-mediated Disordersmentioning
confidence: 87%
“…The possible functional relationship between soluble HLA-G and T cell-IL-4 production was also suggested by the presence of sHLA-G in serum of allergic patients (46,47). Allergy is a disorder characterized by an increased ability of B cells to produce IgE to certain groups of ubiquitous Ags (allergens).…”
Section: Discussionmentioning
confidence: 99%
“…IgE Ab synthesis results from the production of IL-4 by the Th2 cells, which induces the production of IgE by B cells, whereas Th1 cells produce IFN-g that suppresses IgE synthesis (48). Higher levels of sHLA-G in the serum of patients with allergic rhinitis and in allergic children with asthma compared with healthy donors have been reported (46,47). In contrast, sublingual immunotherapy, which was associated with a Th1-type response in patients with allergic rhinitis, was associated with reduced serum levels of sHLA-G (49).…”
Section: Discussionmentioning
confidence: 99%
“…These changes include the induction of immune Tregs as well as changes in the cytokine profile [7]. Furthermore, some studies have reported changes in the immunoregulatory HLA class Ib protein HLA-G [31,32,33,34,35]. The overall objective of the present study was to investigate changes in these parameters in patients who received SIT as an allergy treatment and to compare the changes in the parameters to those observed in healthy nonatopic controls.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HLA-G can induce a T H 2-like cytokine profile in PBMCs and trigger the production of cytokines such as IL-4 and IL-13 [30] that promote antibody isotype switching to IgE. Recent studies have shown that sHLA-G levels are significantly higher in atopic asthmatic and allergic patients compared to healthy nonatopic individuals [31,32]. Furthermore, serum levels of sHLA-G decrease after sublingual immunotherapy (SLIT), while production of the T H 1-cytokine IFN-γ increases [33].…”
Section: Introductionmentioning
confidence: 99%